PENERAPAN ALGORITMA ANT COLONY OPTIMIZATION (ACO) RUTE TERPENDEK STUDI KASUS DISTRIBUSI MINYAK GORENG TOKO CAHAYA BERKAH - Putri Haidi, Melani; Affandi, Pardi (Equiva Journal, 2025)
Cooking oil distribution is one of the important logistics services that requires an optimal delivery route to improve time efficiency and reduce operational costs. This study uses the Ant Colony Optimization (ACO) Algorithm to optimize the cooking oil distribution route from Toko Cahaya Berkah to several destination locations. Distance data between locations was obtained through Google Maps and analyzed using a quantitative approach based on ACO. The Ant Colony Optimization (ACO) algorithm imitates the behavior of an ant colony in finding the shortest path through the pheromone mechanism. The results show that this algorithm is able to find the best distribution route with a route length of 52.14 km, which is the shortest route among the routes evaluated. Pheromone evaporation helps explore wider solutions, thus avoiding convergence on less than optimal local solutions. This study proves that ACO is an effective method for optimizing distribution routes. Assuming normal road conditions and no external obstacles, this algorithm has succeeded in saving travel time and costs significantly. These results are relevant in the context of logistics, especially to improve the efficiency of cooking oil delivery.